Federalism and Individual Liberties—Can We Have Both? - Simon E. Sobeloff (Washington University Law Quarterly, 1965)
Since the sponsors of the Lecture have generously put no restrictions upon me in the choice of a theme, I have thought it appropriate to speak of one aspect of the perennial debate about our federalism, our system of dual sovereignties, national and state. I will examine with you the problem respecting the sometimes apparently conflicting claims of the states in a federal system on the one hand, and on the other the liberties of the individual. I will confine my discussion to the liberties pertaining to criminal due process, leaving for another day those involved in civil rights demonstrations, controversies over school prayers, reapportionment and like concerns.
Keywords: Civil rights; Jurisprudence